2011
DOI: 10.1108/13673271111119655
|View full text |Cite
|
Sign up to set email alerts
|

Integrated socio‐technical knowledge management model: an empirical evaluation

Abstract: Purpose -The purpose of this paper is to examine the validity of the proposed integrated socio-technical knowledge management (KM) model, and to determine the relative importance of social and technical initiatives in organizational KM.Design/methodology/approach -The conceptual model was proposed with three inter-related concepts (knowledge stocks, processes, and socio-technical enablers) and was tested via a survey-based study in the context of public administration of a small European country using 185 seni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 14 publications
2
47
1
2
Order By: Relevance
“…However, these business benefits are not clearly seen within the government organisation culture where it is believed that complex government policies create basic challenges that prevent smooth and active exchange of knowledge from even effectively transferring tacit knowledge within it [3] [20]. Handzic [21] emphasises that even the GO's complex interactions influences the knowledge stocks of the organisation. Three studies on the Malaysian government showed a need for knowledge sharing practices, after knowledge economy strategy that was set ten years ago [10] [22].…”
Section: Km Influence On Government Organizations and Their Initiativesmentioning
confidence: 99%
“…However, these business benefits are not clearly seen within the government organisation culture where it is believed that complex government policies create basic challenges that prevent smooth and active exchange of knowledge from even effectively transferring tacit knowledge within it [3] [20]. Handzic [21] emphasises that even the GO's complex interactions influences the knowledge stocks of the organisation. Three studies on the Malaysian government showed a need for knowledge sharing practices, after knowledge economy strategy that was set ten years ago [10] [22].…”
Section: Km Influence On Government Organizations and Their Initiativesmentioning
confidence: 99%
“…Information technology has been suggested as an important factor in knowledge repositories, data mining, decision support systems, storage and easily retrieval of knowledge resources (Handzic, 2011). I.T has been useful in connecting people to information and has enhanced communication flow among employees of organizations.…”
Section: Circle 5: Choose the Right Km Technologymentioning
confidence: 99%
“…This model emphasised the operative ways to generate the right knowledge and the effective ways to use organizational knowledge. Interestingly, widely-adopted taxonomy of KM recognizes three schools of thought namely: behavioral, economic and technocratic (Handzic, 2011). In a bid to provide a simple and more applicable model for practitioners necessitated the introduction of the 7-circle model.…”
Section: Previous Theories and Models Of Knowledge Managementmentioning
confidence: 99%
“…Further, CSR communication has become synonymous with Corporate Disclosure. [6] Communication needs to be taken seriously among the promising interventions to build on stakeholder communication, pro-active reporting, building trust, and organizing multi-stakeholders voice.…”
Section: Reinforcing Responsible Communicationmentioning
confidence: 99%